Analysis of gunshot residue deposited on cloth target originating from single type of ammunition and pistol / Mohamed Izzharif Abdul Halim and Prof. Madya Dr. Halila Jasmani - Abdul Halim, Mohamed Izzharif; Jasmani, Halila (Research Management Institute (RMI), 2011)
The study of gunshot residue (GSR) has become imperative in forensic firearm examination. It may be used to estimate firing distance, to identify bullet holes and to determine whether or not a person has discharged a firearm. This study emphasized on the examination of the pattern of GSR particle deposited on cotton cloth target at varying shooting distances. Single type of pistol (semiautomatic) and ammunition (Syarikat Malaysia Explosive (SME)) are used for the shooting test. All shooting tests were performed at Lapang Sasar of Palapes, UiTM. The results show that GSR particles produced at shorter distance give more intense and small diameter compared to longer distance produced by same type of pistol and ammunition. The nitrite residues were confirmed by using modified Griess test. It indicated the presence of nitrite residues on the cloth target.The orange coloration became broader in diameter and less intense with increasing shooting distance. Scanning Electron Microscope (SEM) micrographs of GSR particles discharged from SME 9 mm ammunition revealed a mean particle size of 1.5 μm with spherical shapes.